A Nonlinear Blind Source Separation Method Based On Radial Basis Function and Quantum Genetic Algorithm - Wang Pidong; Tang Ruoyun; Zhao Di; Li Hongyi; Chen Jiaxin (MATEC Web of Conferences, 2016)
Blind source separation is a hot topic in signal processing. Most existing works focus on dealing with linear combined signals, while in practice we always encounter with nonlinear mixed signals. To address the problem of nonlinear source separation, in this paper we propose a novel algorithm using radial basis function neutral network, optimized by multi-universe parallel quantum genetic algorithm. Experiments show the efficiency of the proposed method.